Evaluasi Kualitas Layanan Berdasarkan House of Quality : Studi Kasus Cafe di Bandung - Gandhi Pawitan; Vivi Bunga Ratih (Business Administration Department - Universitas Katolik Parahyangan, 2012)
Service quality of the restaurant operations is a focus in this paper. Two Cafe Restau-rants were chosen, one as an research object - Cafe X, and other as its competitor- Cafe Y. Customer satisfaction is observed from the customer of Cafe X, and de-veloped a House of Quality from all this data. The result showed that all of qualityaspects have high importance rate which is explained that all of quality aspect areimportance for customer and has an impact to their satisfaction. The result alsoshowed some customer gave a lower satisfaction performance for some quality as-pects that explained competitors had a better performance. The study provided somesuggestions to increase satisfaction performance with quality service development.Keywords: service quality, service quality measurement, house of quality